The Evaluation of Multiple Sclerosis Dispersal in Iran and Its Association with Urbanization, Life Style and Industry - Rouhullah DEHGHANI; Masoud YUNESIAN; MohammadAli SAHRAIAN; HamidReza GILASI; Vahid KAZEMI-MOGHADDAM (Tehran University of Medical Sciences, 2015)
Background: Multiple Sclerosis (MS) is an autoimmune disease with unknown factor. The prevalence and incidence rate of this disease had an upward trend in many regions in the world such as Middle east and consequently in Iran over the recent years. As the risk factors of this increased trend and high-prevalence is unknown in Iran, the current study has been designed to evaluate the correlation between MS dispersal with urbanization, life style and industry, as an ecological research. Methods: This retrospective study was designed as an ecological approach in 2011. Data were collected from three databases by high precision (CI95%) from national registry plans. The subjects of study were provinces of Iran (n=31). The linear regression was used to perform statistical analyses. Results: The obtained results indicated an ascendant trend of MS during the recent years, as the incidence of this dis-ease reached from 26.24/100000 (CI95%) people in 2006 to 44.53/100000 (CI95%) in 2011. There is a direct correla-tion (P<0.05) between the percentage of urbanization and the percentage of male smokers with the prevalence of MS in provinces. Conclusion: The role of smoking was more highlighted in this study as a probable factor in increasing risk and caus-ing MS disease. Urbanization could be introduced as an augmentative factor, but this is a combination of several com-plex factors that this effect must be appraised with smaller scale in other researches.